ANTIOXIDANT-VITAMIN C: LUNG FUNCTION; LUNG CANCER - Farooqui, Mazahar; Pardeshi, Rajendra; Jadhav, Santosh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Non-enzymatic vitamin C (ascorbic acid) plays an important role in the medicinal field and acts as antioxidants use in fruits and vegetable such as lemon, orange, grapes, carrots, tomatoes, grapefruit, beans, broccoli, and mangos. It helps to prevent and stop of various diseases such as lung cancer, asthma, and wheezing and finding an antibronchospastic effect. Other factors such as diet have also been implicated in the development of lung cancer. Despite the extensive research conducted in this area, the relationship between diet and lung cancer is still not clear. Diets high in fat and low in vegetables and fruits may increase the risk of lung cancer and other fact eating of tobacco and smoking of cigarette. Lung tissue damage due to high levels of free radicals in cigarette smoke causes direct (tissue oxidation) and indirect (release of oxidizing agents and enzymes). Vitamin C is necessary for phagocytosis. It plays a significant role in daily life, dietary system like eating food, vegetable and smoking of cigarette. It helps to prevent or stop the damage the lung tissue/or cause lung cancer. The present review studied that application of vitamin C act as antioxidant in lung cancer like diseases such as lung-cancer and role in lung function. Keywords: Review, Non-enzymatic antioxidant (vitamin C), Lung function, Lung diseases.